Effect of fair value accounting for financial instruments on the decision usefulness of reported earnings - Chong, Leong Yew (2018)
At present, the decision usefulness of fair value accounting is still very much debated among academicians. Given the ongoing debates and the limited evidence available, it is still an open question as to whether Fair Value Accounting (FVA) for financial instruments enhances or impairs the decision usefulness of reported earnings. This study is undertaken to examine the effects of FVA for financial instruments on the decision usefulness of reported earnings for financial firms in the Asia Pacific region under IFRS environment. This study also examines whether corporate governance mechanisms moderate the relationship between FVA for financial instruments and reported earnings. Furthermore, the impact of country-level legal enforcement on the relationship between FVA for financial instruments and reported earnings is also examined. This study contributes to the literature on whether the shift from Historical Cost Accounting (HCA) to FVA enhances the decision usefulness of reported earnings. Data for a sample of 480 firm-year observations were hand-collected from the listed financial firms from three countries namely Hong Kong, Singapore, and Malaysia in the Asia Pacific region over the 5-year period from 2012 to 2016. This study uses Panel Data and Hierarchical Regression Analysis Techniques to examine the objective of this study, which is the effects of fair value accounting for financial instruments on the decision usefulness of reported earnings. Due to the statistically insignificant results, this study establishes that there is not enough evidence to conclude that the Adjusted Comprehensive Income (ACI) has more predictive power than Net Income (NI) on future Operating Cash Flows (CFO) and future NI. With regard to value relevance, the results also show that there is not enough evidence to suggest that ACI is more value relevant than NI for both share prices and share returns as the results are statistically insignificant. As for the strength of Corporate Governance mechanisms, the results show that the strength of CG mechanisms positively moderates the predictive power of financial instruments’ fair values on future CFO. The results also show that the strength of CG mechanisms positively moderate the value relevance of financial instruments’ fair values on share prices. As for the stronger country-level enforcement, the results, however, show that stronger country-legal enforcement in developed countries negatively moderates the predictive power of financial instruments’ fair values on future CFO. The results also show that stronger country-legal enforcement in developed countries positively moderates the value relevance of financial instruments’ fair values on share returns. The findings of this study have implications on the investors, shareholders, standard setters, policy makers, and regulators. The reporting fair value changes in financial instrument components in Other Comprehensive Income can be regarded as decision useful information. This may imply that investors may need to pay attention to the fair value reporting for financial instrument components when making investment decisions. The results from the study may benefit the standard setter such as IASB as it provides empirical evidence on the use of accounting standards for countries in the Asia Pacific region where the institutional factors (e.g., ownership structures and legal enforcement) may be different from the developed countries such as US, UK, and Europe. In addition, the findings of this study may provide useful information and may benefit the policy makers and regulators.